Mathematical Analysis of a Reactive Viscous Flow through a Channel Filled with a Porous Medium. (27th December 2016) - Adesanya, Samuel O.; Falade, J. A.; Ukaegbu, J. C.; Adekeye, K. S.
Abstract : An investigation has been carried out to study entropy generation in a viscous, incompressible, and reactive fluid flowing steadily through a channel with porous materials. Approximate solutions for both velocity and temperature fields are obtained by using a rapidly convergent Adomian decomposition method (ADM). These solutions are then used to determine the heat irreversibility and Bejan number of the problem. Variations of other important fluid parameters are conducted, presented graphically, and discussed.